Perception of influence of digital technology on occupational health safety training among academic staff in Nigerian universities (2021)
Academic are busy to participate in physical OHS training because of many engagements with their students, administrative work and community service. As a result, they hardly find time to give proper attention to germane issues as their safety and health. This then calls for the use of digital technology to organise OHS training as it is expected to help these busy group of people incorporate the training alongside their busy schedule. The study examined the perceived influence of digital technology on occupational health safety training among academic staff in Nigerian universities. Five specific objectives with corresponding research questions were achieved and answered. Descriptive survey research design was employed and convenience sampling technique through on-line questionnaire was used to obtain information from the targeted respondents. One hundred well filled on-line surveys were analysed with the aid of descriptive statistics. The empirical findings indicated that the respondents expressed adequate knowledge about the occupation health hazard associated with their profession but had low exposure to the application of digital technology such as 3D visualization and Virtual Reality (VR). The study revealed that the digital technology influenced Occupational Health and Safety (OHS) training, but the academic staff encountered hindrances with the use of digital technology training for OHS training. It is concluded that digital technology played a vital role towards OHS training and there is a need for regular capacity programmes using digital technology tools which aimed at helping management to address OHS needs of academic staff.